(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The agendas for Climate Change and for Sustainable Development launched in Paris and New York in 2015 set a fundamental milestone in the efforts that countries, international institutions, civil society and individual people endeavor to make in order to build a global sustainable equilibrium which balances the economic, social and environmental dimensions, which does not compromise the well-being of future generations while pursuing a just, fair and safe space for humanity in the coming decades. Both agendas, as well as both issues, are complexly interrelated and require a coordinated effort towards action and innovation to achieve their multiple objectives.